CsbZIP2-miR9748-CsNPF4.4 Module Mediates High Temperature Tolerance of Cucumber Through Jasmonic Acid Pathway - Li, Lan; Chen, Guangling; Yuan, Mingzhu; Guo, Shirong; Wang, Yu; Sun, Jin (Frontiers in Plant Science, 2022)
High temperature stress seriously affects the growth of cucumber seedlings, and even leads to a decline in yield and quality. miRNAs have been shown to be involved in regulating the response to stress in plants, but little is known about its effects on cucumber high temperature stress tolerance. Here, we found that high temperature stress induced the expression of miR9748 in cucumber. Overexpression of cucumber miR9748 in Arabidopsis improved high temperature tolerance. Transcriptome analysis revealed that miR9748 might mediate high temperature tolerance through plant hormone signal pathway. 5' RNA ligase-mediated rapid amplification of cDNA ends (5' RLM-RACE) and transient transformation technology demonstrated that CsNPF4.4 was the target gene of miR9748. CsNPF4.4 overexpression plants decreased high temperature tolerance accompanied by reducing the content of jasmonic acid (JA), but alleviated by foliar application of methyl jasmonate, indicating that CsNPF4.4 negatively regulated high temperature stress tolerance through inhibition JA signal pathway. Furthermore, high temperature stress also increased the expression level of CsbZIP2. Yeast one-hybrid and dual luciferase assays showed that CsbZIP2 directly bound to the promoter of MIR9748 to induce its expression. Taken together, our results indicated that CsbZIP2 directly regulated miR9748 expression to cleave CsNPF4.4 to mediate high temperature tolerance through JA pathway.